Commodity trading advisors : risk, performance analysis, and selection - Gregoriou, Greg N., 1956- (Wiley, 2004)
Authoritative, up-to-date research and analysis that provides a dramatic new understanding of the rewards-and risks-of investing in CTAsCommodity Trading Advisors (CTAs) are an increasingly popular and potentially profitable investment alternative for institutional investors and high-net-worth individuals.